Anti-cracking low-smoke halogen-free flame-retardant sheath material and preparation method thereof

By using a mixture of materials such as ethylene-vinyl acetate copolymer and silane coupling agent, a low-smoke-resistant halogen-free flame-retardant sheath material is prepared, which solves the problem of insufficient mechanical properties and flame retardant properties of existing cable sheath materials, and achieves higher mechanical properties and flame retardant properties, reducing cracking phenomenon.

CN119823469AInactive Publication Date: 2025-04-15DINGZHOU ZHONGSHUO PLASTIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510039930.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

While the existing cable sheath materials pursue flame retardant properties, their mechanical properties and fluidity are deteriorated, making them prone to cracking problems, especially in extreme climates.

Method used

A mixture of ethylene-vinyl acetate copolymer, metallocene low-density polyethylene and ethylene-octene copolymer is used as the matrix resin, and a silane coupling agent is added to prepare a crack-resistant low-smoke, halogen-free flame-retardant sheath material through intensive refining and extrusion granulation processes.

Benefits of technology

It improves the mechanical properties and flame retardancy of the sheath material, significantly reduces cracking, and ensures that stable performance can be maintained under extreme climate conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005236627980000081
    Figure BDA0005236627980000081
Patent Text Reader

Abstract

The invention discloses an anti-cracking low-smoke halogen-free flame-retardant sheath material and a preparation method thereof. The anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 30-40 parts of matrix resin, 8-10 parts of a compatilizer, 50-60 parts of a flame retardant, 0.4-1 part of an antioxidant, 0.5-1.6 parts of a lubricant, 1-3 parts of carbon black master batch and 1-3 parts of a silane coupling agent. Wherein the matrix resin is a mixture of an ethylene-vinyl acetate copolymer, metallocene linear low density polyethylene and an ethylene-octene copolymer. By adopting the formula provided by the invention, the problems that the existing sheath material is poor in mechanical property and easy to crack can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of halogen-free flame-retardant materials, in particular to a crack-resistant low-smoke halogen-free flame-retardant sheath material and a preparation method thereof. Background Art

[0002] In recent years, with the increasing global environmental awareness, halogen-free flame retardants, as a new generation of environmentally friendly flame retardant materials, are gradually replacing traditional halogen flame retardants and becoming the new favorite in the flame retardant field. Compared with halogen flame retardants, halogen-free flame retardants do not produce toxic and harmful hydrogen halide gas during combustion, thereby significantly reducing the potential harm to the environment and human body. The small amount of smoke generated during combustion not only improves safety, but also reduces the adverse effects of smoke on rescue operations. Halogen-free flame retardants not only have excellent flame retardant properties and can effectively suppress the spread of fire at high temperatures, but also show good thermal stability and light stability, ensuring that they can still exert a stable flame retardant effect under complex and changing environmental conditions. These excellent properties make halogen-free flame retardants occupy a pivotal position in the cable industry, especially in the research and development and application of halogen-free low-smoke flame retardant materials.

[0003] While the current cable products on the market pursue flame retardant properties, there are also some problems. In order to meet the established flame retardant standards, sufficient inorganic halogen-free flame retardants are often added to the sheath material. However, the large amount of inorganic flame retardants often deteriorates the mechanical properties and fluidity of the material, causing the cable to crack easily during use. Especially under extreme climatic conditions such as high temperature and severe cold, such problems are particularly prominent, which not only affects the service life of the cable, but also may pose a potential threat to the stable operation of the power system.

[0004] Therefore, it is necessary to develop a crack-resistant low-smoke halogen-free flame-retardant sheath material to solve the above problems. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies in the prior art, the present invention provides a crack-resistant low-smoke halogen-free flame-retardant sheath material and a preparation method thereof, which improves the mechanical properties and flame retardancy of the product sheath material and avoids the problem of cracking during use.

[0007] (II) Technical solution

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The invention discloses a crack-resistant low-smoke halogen-free flame-retardant sheath material, comprising the following components in parts by weight: 30-40 parts of base resin, 8-10 parts of compatibilizer, 50-60 parts of flame retardant, 0.4-1 parts of antioxidant, 0.5-1.6 parts of lubricant, 1-3 parts of carbon black masterbatch, and 1-3 parts of silane coupling agent;

[0010] The base resin is a mixture of ethylene-vinyl acetate copolymer, metallocene linear low-density polyethylene and ethylene-octene copolymer.

[0011] Furthermore, the VA content of the ethylene-vinyl acetate copolymer is 28%, and the melt index is 3-6.

[0012] Furthermore, the mass percentage of the ethylene-vinyl acetate copolymer in the matrix resin is 30% to 45%, the mass percentage of the metallocene linear low-density polyethylene in the matrix resin is 35% to 45%, and the mass percentage of the ethylene-octene copolymer in the matrix resin is 25% to 35%.

[0013] Furthermore, the compatibilizer is one or both of metallocene polyethylene grafted maleic anhydride copolymer and polyethylene grafted maleic anhydride copolymer.

[0014] Furthermore, the flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide, and the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1:3.

[0015] Furthermore, the magnesium hydroxide is surface-modified ultrafine magnesium hydroxide.

[0016] Furthermore, the antioxidant is a mixture of antioxidant 1010 and antioxidant DLTP, and the mass ratio of the antioxidant 1010 to the antioxidant DLTP is 3:1.

[0017] Furthermore, the lubricant is one or both of polyethylene wax and stearic acid.

[0018] Furthermore, the carbon black content in the carbon black masterbatch is 40% to 50%.

[0019] The present invention also discloses a method for preparing a crack-resistant low-smoke halogen-free flame-retardant sheath material, comprising the following steps:

[0020] S1. Put the raw materials in batches according to the ratio strictly, mix them evenly, then pressurize the mixer to 120℃, start the pressure hammer to make the material mass roll so that the material mass is evenly dispersed, repeat 3 to 4 times, the overall mixing time is 12 to 15 minutes, and the temperature reaches 160℃ to make the material mass plasticized evenly;

[0021] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0022] (III) Beneficial technical effects

[0023] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects:

[0024] (1) The present invention adopts a mixture of ethylene-vinyl acetate copolymer, metallocene low-density polyethylene and ethylene-octene copolymer as the matrix resin, and the molecular chains of ethylene-vinyl acetate copolymer, metallocene low-density polyethylene and ethylene-octene copolymer will be mutually entangled and interpenetrated in the molten state to form a tight network structure. At the same time, the molecular chain of ethylene-vinyl acetate copolymer contains vinyl acetate groups, and these polar groups can interact with the non-polar parts in the metallocene low-density polyethylene and ethylene-octene molecular chains to form hydrogen bonds or dipole-dipole interactions, which can enhance the bonding between molecular chains. Through the entanglement and interpenetration of the molecular chain segments and the interaction of the polar groups, the tensile strength and tear strength of the sheath material can be enhanced, and the mechanical properties and crack resistance of the sheath material can be improved.

[0025] (2) The present invention adds a silane coupling agent, and one end of the molecular structure of the silane coupling agent reacts with magnesium hydroxide or aluminum hydroxide, and the other end can react with the matrix resin. This molecular structure enables the silane coupling agent to build a "molecular bridge" between the inorganic and organic cross-sections, thereby improving the binding force between the two. At the same time, through the coupling effect of the silane coupling agent, the interfacial tension between the inorganic split and the matrix resin can be reduced, and their compatibility can be improved. It helps to separate the inorganic flame retardant from the organic matrix resin, making the mixture more uniform and stable. Improve the effective combination of the inorganic flame retardant and the organic matrix resin. DETAILED DESCRIPTION

[0026] To achieve the above object, the present invention provides the following specific implementation methods and embodiments:

[0027] Example 1

[0028] A crack-resistant low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 30 parts of base resin, 8 parts of compatibilizer, 50 parts of flame retardant, 0.4 parts of antioxidant, 0.5 parts of lubricant, 1 part of carbon black masterbatch and 1 part of silane coupling agent.

[0029] in,

[0030] Base resin: 10 parts of ethylene-vinyl acetate copolymer, 11 parts of metallocene low-density polyethylene and 9 parts of ethylene-octene copolymer.

[0031] Compatibilizer: 8 parts of metallocene polyethylene grafted maleic anhydride copolymer.

[0032] Flame retardant: 12.5 parts of magnesium hydroxide and 37.5 parts of aluminum hydroxide.

[0033] Antioxidant: 0.3 parts of antioxidant 1010 and 0.1 parts of antioxidant DLTP.

[0034] The silane coupling agent is silane coupling agent 172.

[0035] The method for preparing the above-mentioned anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following steps:

[0036] S1. Place the above raw materials in batches according to the ratio, mix them evenly, and then pressurize the mixer to 120°C, and use the pressure hammer to make the material mass roll so that the material mass is evenly dispersed. Repeat 3 times. The overall mixing time is 12 minutes, and the temperature reaches 160°C to make the material mass plasticized evenly.

[0037] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0038] Example 2

[0039] A crack-resistant low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 30 parts of base resin, 8 parts of compatibilizer, 50 parts of flame retardant, 0.4 parts of antioxidant, 0.5 parts of lubricant, 1 part of carbon black masterbatch and 1 part of silane coupling agent.

[0040] in,

[0041] Base resin: 10 parts of ethylene-vinyl acetate copolymer, 11 parts of metallocene low-density polyethylene and 9 parts of ethylene-octene copolymer.

[0042] Compatibilizer: 8 parts of polyethylene grafted maleic anhydride copolymer.

[0043] Flame retardant: 12.5 parts of magnesium hydroxide and 37.5 parts of aluminum hydroxide.

[0044] Antioxidant: 0.3 parts of antioxidant 1010 and 0.1 parts of antioxidant DLTP.

[0045] The silane coupling agent is silane coupling agent 172.

[0046] The method for preparing the above-mentioned anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following steps:

[0047] S1. Place the above raw materials in batches according to the ratio, mix them evenly, and then pressurize the mixer to 120°C, and use the pressure hammer to make the material mass roll so that the material mass is evenly dispersed. Repeat 3 times. The overall mixing time is 12 minutes, and the temperature reaches 160°C to make the material mass plasticized evenly.

[0048] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0049] Example 3

[0050] A crack-resistant low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 35 parts of base resin, 9 parts of compatibilizer, 55 parts of flame retardant, 0.7 parts of antioxidant, 1 part of lubricant, 2 parts of carbon black masterbatch, and 2 parts of silane coupling agent.

[0051] in,

[0052] Base resin: 12 parts of ethylene-vinyl acetate copolymer, 13 parts of metallocene low-density polyethylene and 10 parts of ethylene-octene copolymer.

[0053] Compatibilizer: 5 parts of metallocene polyethylene grafted maleic anhydride copolymer and 4 parts of polyethylene grafted maleic anhydride copolymer.

[0054] Flame retardant: 14 parts of magnesium hydroxide and 41 parts of aluminum hydroxide.

[0055] Antioxidant: 0.5 parts of antioxidant 1010 and 0.2 parts of antioxidant DLTP.

[0056] The silane coupling agent is silane coupling agent 172.

[0057] The method for preparing the above-mentioned anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following steps:

[0058] S1. Place the above raw materials in batches according to the ratio, mix them evenly, and then pressurize the mixer to 120°C, and use the pressure hammer to make the material mass roll so that the material mass is evenly dispersed. Repeat 4 times. The overall mixing time is 13 minutes. The temperature reaches 160°C to make the material mass plasticized evenly.

[0059] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0060] Example 4

[0061] A crack-resistant low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 40 parts of base resin, 10 parts of compatibilizer, 60 parts of flame retardant, 1 part of antioxidant, 1.6 parts of lubricant, 3 parts of carbon black masterbatch, and 3 parts of silane coupling agent.

[0062] in,

[0063] Base resin: 14 parts of ethylene-vinyl acetate copolymer, 15 parts of metallocene low-density polyethylene and 11 parts of ethylene-octene copolymer.

[0064] Compatibilizer: 5 parts of metallocene polyethylene grafted maleic anhydride copolymer and 5 parts of polyethylene grafted maleic anhydride copolymer.

[0065] Flame retardant: 15 parts of magnesium hydroxide and 45 parts of aluminum hydroxide.

[0066] Antioxidant: 0.75 parts of antioxidant 1010 and 0.25 parts of antioxidant DLTP.

[0067] The silane coupling agent is silane coupling agent 172.

[0068] The method for preparing the above-mentioned anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following steps:

[0069] S1. Place the above raw materials in batches according to the ratio, mix them evenly, and then pressurize the mixer to 120°C, and use the pressure hammer to make the material mass roll so that the material mass is evenly dispersed. Repeat 4 times. The overall mixing time is 15 minutes. The temperature reaches 160°C to make the material mass plasticized evenly.

[0070] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0071] Example 5

[0072] A crack-resistant low-smoke halogen-free flame-retardant sheath material comprises the following components in parts by weight: 40 parts of base resin, 10 parts of compatibilizer, 60 parts of flame retardant, 1 part of antioxidant, 1.6 parts of lubricant, 3 parts of carbon black masterbatch, and 3 parts of silane coupling agent.

[0073] in,

[0074] Base resin: 11 parts of ethylene-vinyl acetate copolymer, 15 parts of metallocene low-density polyethylene and 14 parts of ethylene-octene copolymer.

[0075] Compatibilizer: 5 parts of metallocene polyethylene grafted maleic anhydride copolymer and 5 parts of polyethylene grafted maleic anhydride copolymer.

[0076] Flame retardant: 15 parts of magnesium hydroxide and 45 parts of aluminum hydroxide.

[0077] Antioxidant: 0.75 parts of antioxidant 1010 and 0.25 parts of antioxidant DLTP.

[0078] The silane coupling agent is silane coupling agent 172.

[0079] The method for preparing the above-mentioned anti-cracking low-smoke halogen-free flame-retardant sheath material comprises the following steps:

[0080] S1. Place the above raw materials in batches according to the ratio, mix them evenly, and then pressurize the mixer to 120°C, and use the pressure hammer to make the material mass roll so that the material mass is evenly dispersed. Repeat 4 times. The overall mixing time is 15 minutes. The temperature reaches 160°C to make the material mass plasticized evenly.

[0081] S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.

[0082] The sheath materials produced in Examples 1 to 5 were subjected to performance tests. The tensile strength and elongation at break were tested according to GB / T1040.2-2006 standard, and the oxygen index was tested according to GB / T2406.2-2009 standard. The specific test results are shown in Table 1.

[0083] Table 1: Performance test results of sheath materials

[0084]

[0085] It can be seen from Table 1 that the oxygen index of the sheath material provided in the embodiment of the present invention is greater than 30%, the tensile strength is greater than 13 MPa, and the elongation at break is greater than 160%. The sheath material of the present invention has strong mechanical properties and flame retardancy, among which Example 5 has the best effect.

[0086] Although the present application has been described with reference to its preferred specific embodiments, those skilled in the art should understand that various changes can be made without departing from the true spirit and scope of the present application. For example, the subject, spirit and scope of the present application can be changed in various ways to adapt to specific situations, materials, material combinations or method steps. All of these changes are included in the scope of the claims of the present application. And making slight changes or modifications using the above-disclosed technical content is equivalent to equivalent implementation cases and falls within the scope of the technical solution.

Claims

1. A crack-resistant low-smoke halogen-free flame-retardant sheath material, characterized by: The invention comprises the following components in parts by weight: 30-40 parts of base resin, 8-10 parts of compatibilizer, 50-60 parts of flame retardant, 0.4-1 parts of antioxidant, 0.5-1.6 parts of lubricant, 1-3 parts of carbon black masterbatch and 1-3 parts of silane coupling agent; The base resin is a mixture of ethylene-vinyl acetate copolymer, metallocene linear low-density polyethylene and ethylene-octene copolymer.

2. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The VA content of the ethylene-vinyl acetate copolymer is 28%, and the melt index is 3-6.

3. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The mass percentage of the ethylene-vinyl acetate copolymer in the base resin is 30% to 45%, the mass percentage of the metallocene linear low-density polyethylene in the base resin is 35% to 45%, and the mass percentage of the ethylene-octene copolymer in the base resin is 25% to 35%.

4. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The compatibilizer is one or both of a metallocene polyethylene grafted maleic anhydride copolymer and a polyethylene grafted maleic anhydride copolymer.

5. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The flame retardant is a mixture of magnesium hydroxide and aluminum hydroxide, and the mass ratio of the magnesium hydroxide to the aluminum hydroxide is 1:

3.

6. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 5, characterized in that: The magnesium hydroxide is surface-modified ultrafine magnesium hydroxide.

7. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The antioxidant is a mixture of antioxidant 1010 and antioxidant DLTP, and the mass ratio of the antioxidant 1010 to the antioxidant DLTP is 3:

1.

8. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The lubricant is one or both of polyethylene wax and stearic acid.

9. The anti-cracking low-smoke halogen-free flame-retardant sheath material according to claim 1, characterized in that: The carbon black content in the carbon black masterbatch is 40% to 50%.

10. The method for preparing the crack-resistant low-smoke halogen-free flame-retardant sheath material according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Put the raw materials in batches according to the ratio strictly, mix them evenly, then pressurize the mixer to 120℃, start the pressure hammer to make the material mass roll so that the material mass is evenly dispersed, repeat 3 to 4 times, the overall mixing time is 12 to 15 minutes, and the temperature reaches 160℃ to make the material mass plasticized evenly; S2. The material mass plasticized evenly in the internal mixer in S1 is put into the elevator, which is then poured into the conical double-style forced feeder. The feeder evenly squeezes the material mass into the twin-screw extruder for full plasticization and dispersion, and then enters the single-screw extruder for extrusion granulation. The material is transported by a fan, cooled, dried, screened, stored in a warehouse, and then automatically and semi-automatically vacuum packaged to obtain a crack-resistant, low-smoke, halogen-free, flame-retardant sheath material.